Legal Challenges in Protecting Uzbekistan’s Cultural Heritage - Mukhitdinova, Firyuza Abdurashidovna (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2025)
The protection of historical and cultural heritage is a crucial aspect of preserving national identity and safeguarding a nation's historical values. Uzbekistan, as a country with a rich cultural heritage, has established various national regulations and holds membership in international conventions to protect its cultural assets. However, the implementation of these policies faces multiple challenges, including a lack of inter-agency coordination and resource constraints. This study aims to analyze the national and international legal frameworks for cultural heritage protection in Uzbekistan. It employs a normative legal research method with a descriptive-analytical approach. Data is obtained through document analysis of national regulations, such as the Law on the Protection and Use of Cultural Heritage Objects, as well as international agreements, including the 1972 UNESCO World Heritage Convention. The analysis is conducted through content analysis of legal texts and policies, along with a comparative approach to assess the effectiveness of national regulations against international standards. The study finds that although Uzbekistan has established a strong legal foundation for cultural heritage protection, policy implementation continues to face challenges, including regulatory inefficiencies, weak law enforcement, and limited public awareness of the importance of cultural heritage preservation. Furthermore, despite Uzbekistan's adoption of various international conventions, the harmonization of domestic laws with international standards remains inadequate. Therefore, more progressive legal reforms, enhanced law enforcement capacity, and the optimization of oversight mechanisms are necessary to ensure more effective cultural heritage protection.